Vibration and buckling characteristics of cracked natural fiber reinforced composite plates with corner point-supports. (1st July 2020) - Xu, Chenghui; Rong, Dalun; Zhou, Zhenhuan; Deng, Zichen; Lim, C.W.
Highlights: New symplectic analytical solutions for vibration and buckling of cracked plates are derived and presented. Exact solutions for natural fiber reinforced composite (NFRC) plates with a partial or an internal crack are established. Significant influence of crack parameters and hygrothermal ageing on the vibration and buckling behavior are discussed. The result concludes the significant effects of crack length and location on the hygrothermal ageing of NFRC plates. Abstract: This paper is concerned with the accurate free vibration and buckling analysis of a partially or internally cracked natural fiber reinforced composite (NFRC) plate with corner point-supports by symplectic elasticity method. Mechanical degradation of NFRC plate during the hygrothermal ageing is described by using a theoretical damage model. Crack effects on the plate derived by using the line spring model (LSM) are considered in the governing equation of motion in the form of crack compliance coefficients. In the framework of symplectic elasticity, free vibration and buckling eigenvalue problems for three types of boundary conditions can be reduced into a set of algebraic equations by a superposition of boundaries. Highly accurate critical buckling loads, fundamental frequencies and corresponding mode shapes are solved simultaneously. A comparison of the new proposed model with finite element method is presented to validate the accuracy and effectiveness of the present method. Subsequently, the influence of hygrothermal ageing and crack parameters on the free vibration and buckling behaviors of cracked NFRC plates is rigorously presented. The research results conclude that both length and crack location are important factors that affect the hygrothermal ageing of NFRC plates.